Protective Effects of Flavonoids Against Mitochondriopathies and Associated Pathologies: Focus on the Predictive Approach and Personalized Prevention - Koklesova, Lenka; Liskova, Alena; Samec, Marek; Zhai, Kevin; Al-Ishaq, Raghad Khalid; Bugos, Ondrej; Šudomová, Miroslava; Biringer, Kamil; Pec, Martin; Adamkov, Marian; Hassan, Sherif T S; Saso, Luciano; et al. (International journal of molecular sciences, 2021)
Multi-factorial mitochondrial damage exhibits a "vicious circle" that leads to a progression of mitochondrial dysfunction and multi-organ adverse effects. Mitochondrial impairments (mitochondriopathies) are associated with severe pathologies including but not restricted to cancers, cardiovascular diseases, and neurodegeneration. However, the type and level of cascading pathologies are highly individual. Consequently, patient stratification, risk assessment, and mitigating measures are instrumental for cost-effective individualized protection. Therefore, the paradigm shift from reactive to predictive, preventive, and personalized medicine (3PM) is unavoidable in advanced healthcare. Flavonoids demonstrate evident antioxidant and scavenging activity are of great therapeutic utility against mitochondrial damage and cascading pathologies. In the context of 3PM, this review focuses on preclinical and clinical research data evaluating the efficacy of flavonoids as a potent protector against mitochondriopathies and associated pathologies.
Keywords: cancer; neurodegeneration; mitochondrie; Antioxidants; anti-oxidant activity; Prognosis; mitofagie; stress; Mitochondrial Diseases; Oxidative Stress; natural substances; flavonoidy; antioxidancia; individualizovaná medicína; predictive preventive personalized medicine (PPPM/3PM); Flavonoids; injury; prognóza; genoprotection; mitochondrial function; Humans; phytochemicals; tumorigenesis; dysfunction; mitochondriopathy; Mitophagy; patient stratification; Mitochondria; Cytoprotection; cardiovascular disease; oxidační stres; Precision Medicine; flavonoids; cytoprotekce; mitochondrial impairment; lidé; mitochondriální nemoci